Evolution of mir-92a Underlies Natural Morphological Variation in Drosophila melanogaster - Arif, Saad (2017)
The deposited article is a post-print version and has peer review. This deposit is composed by the main article, and it hasn't any supplementary materials associated. The supplementary materials are present in the publisher's page in the following link: http://www.sciencedirect.com/science/MiamiMultiMediaURL/1-s2.0-S0960982213001899/1-s2.0-S0960982213001899-mmc1.pdf/272099/html/S0960982213001899/187ecb1b8f94027ceebb87907c58eb3f/mmc1.pdf